The "Ulos" Metaphor in Japanese Diplomacy: A Critical Discourse Analysis of the Japanese Consul General's Speech in Medan (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
This study analyzes the discursive strategies in the Japanese Consul General's speech in Medan during the Emperor of Japan's birthday reception. Using Norman Fairclough's three-dimensional Critical Discourse Analysis (CDA) framework, this research examines how language is employed to construct diplomatic identity and assert Japan's soft-power influence in North Sumatra. This study analyzes official speech manuscripts in Japanese and Indonesian at three levels: textual, discursive practice, and socio-cultural practice. The results show that weaving metaphors (tate-ito and yoko-ito), compared to the traditional Ulos cloth, become tools for ideological localization and naturalizing universal values such as democracy and the rule of law. The speech places empathy narratives about local flood disasters at the beginning, which acts as a discursive positioning strategy to build moral legitimacy (ethos). The study concludes that Japan obscure asymmetrical power relations by framing economic and political interests within a 'heart-to-heart' (kokoro no tomo) friendship narrative rooted in local audience wisdom.
Keywords: Critical Discourse Analysis; Norman Fairclough; Japanese Diplomacy; Ulos Metaphor